2009
DOI: 10.1002/syn.20634
|View full text |Cite
|
Sign up to set email alerts
|

Multitracer assessment of dopamine function after transplantation of embryonic stem cell‐derived neural stem cells in a primate model of Parkinson's disease

Abstract: The ability of primate embryonic stem (ES) cells to differentiate into dopamine (DA)-synthesizing neurons has raised hopes of creating novel cell therapies for Parkinson's disease (PD). As the primary purpose of cell transplantation in PD is restoration of dopaminergic neurotransmission in the striatum, in vivo assessment of DA function after grafting is necessary to achieve better therapeutic effects. A chronic model of PD was produced in two cynomolgus monkeys (M-1 and M-2) by systemic administration of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…We previously confirmed that the degeneration of nigrostriatal dopamine neurons was induced by the intravenous administration of MPTP to monkeys over a period of several months and resulted in impaired presynaptic dopamine parameters, as determined by DAT availability, dopamine synthesis, and tyrosine hydroxylase immunoreactivity in the brain (9,10). A previous study reported that although plotting the striatal MTGA Ki values of 11 C-6MemTyr, b-11 C-L-DOPA, and 18 F-FDOPA against the BP ND of 11 C-b-CFT in the striatum of monkeys revealed positive correlations, the Ki value of 11 C-6MemTyr provided greater correlation coefficients than b-11 C-L-DOPA and 18 F-FDOPA (10).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We previously confirmed that the degeneration of nigrostriatal dopamine neurons was induced by the intravenous administration of MPTP to monkeys over a period of several months and resulted in impaired presynaptic dopamine parameters, as determined by DAT availability, dopamine synthesis, and tyrosine hydroxylase immunoreactivity in the brain (9,10). A previous study reported that although plotting the striatal MTGA Ki values of 11 C-6MemTyr, b-11 C-L-DOPA, and 18 F-FDOPA against the BP ND of 11 C-b-CFT in the striatum of monkeys revealed positive correlations, the Ki value of 11 C-6MemTyr provided greater correlation coefficients than b-11 C-L-DOPA and 18 F-FDOPA (10).…”
Section: Discussionmentioning
confidence: 68%
“…Five male normal and 5 MPTP-treated cynomolgus monkeys (Macaca fascicularis; age range, 2.8-3.3 y; weight range, 2.0-3.5 kg) were subjected to PET scans (9,10). MPTP at doses ranging from 0.2 to 0.4 mg/kg of free base in phosphate-buffered saline was injected intravenously once per week over a 4-mo period until a stable parkinsonian syndrome was observed.…”
Section: Animalsmentioning
confidence: 99%
“…In the 2009 study by Muramatsu and colleagues, dopaminergic neurons differentiated from primate embryonic stem cells were transplanted into MPTP-lesioned cynomolous monkeys. 21 Following transplantation, PET scans showed restored dopamine function in the brain, although there was only modest functional recovery at 12 weeks after implantation.…”
Section: Application For Parkinson's Diseasementioning
confidence: 99%
“…30 Recently, dopaminergic neurons derived from monkey ESCs (using the NSS method) were transplanted into a monkey model of Parkinson disease, and the technique promoted locomotion. 24 We hypothesized that the NSS method could also be applied to iPSCs to achieve targeted differentiation into neuronal cells.…”
mentioning
confidence: 99%
“…Using the NSS method, dopaminergic neurons have been derived from monkey ESCs and have been transplanted to monkeys with Parkinson disease, resulting in improved motor function. 24 Human neurons, generated from ESCs by the NSS method, have been shown to survive in murine brains following xenotransplantation. 34 Nakayama and colleagues 29 reported that the NSS method was very efficient because each ESC generated 1000 NSCs in an 11-day period.…”
mentioning
confidence: 99%